1970
DOI: 10.2135/cropsci1970.0011183x001000040007x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Persistence and Depletion in Buried Seed Populations. II. The Effects of Soil Temperature and Moisture1

Abstract: Field and controlled environment studies were conducted to evaluate the effects of certain environmental factors on the persistence of buried seed of annual ryegrass (Lolium multiflorum Lain.), a free‐volunteering species; and perennial ryegrass (Lolium perenne L.), nonpersistent species. Buried seed of annual ryegrass persisted in both nondormant and dormant condition. Buried seed of perennial ryegrass lost virtually all viability after 60 days of burial in the field. This dissipation occurred largely via in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 0 publications
1
51
0
2
Order By: Relevance
“…If these dispersed seeds in the upper layers were transient, then there must be both continual addition andloss (Keeley 1977),includingpredation (Kjellson 1985;Wellington & Noble 1985), germination followed by unsuccessful establishment, and loss of viability with time (Schafer & Chilcote 1970;Weiss 1984). At some study sites unsuccessful establishment following germination has been observed in bracken stands adjacent to forest, where seedlings of forest species have been seen to survive during winter, but die the following summer.…”
Section: Discussionmentioning
confidence: 99%
“…If these dispersed seeds in the upper layers were transient, then there must be both continual addition andloss (Keeley 1977),includingpredation (Kjellson 1985;Wellington & Noble 1985), germination followed by unsuccessful establishment, and loss of viability with time (Schafer & Chilcote 1970;Weiss 1984). At some study sites unsuccessful establishment following germination has been observed in bracken stands adjacent to forest, where seedlings of forest species have been seen to survive during winter, but die the following summer.…”
Section: Discussionmentioning
confidence: 99%
“…Grey arrows indicate seed movements, and processes related to movement are in bold. After Schafer andChilcote (1970), Fenner (1985), Chambers and Mac Mahon (1994) and Van der Wall et al (2002). The term "seed" used throughout the model and the text represents the diaspore or unit of dispersal (seed with surrounding dispersal structures).…”
Section: Introductionmentioning
confidence: 99%
“…Leck and Graveline (1979) found a decrease in total number of seedlings which germinated from deeper tidal marsh profile samples, but determined that it was not statistically significant. They postulated that the lack of a significant pattern in numbers of viable seeds through the profile supports previous theories that seed viability is prolonged in cool, moist soil conditions (Schafer and Chilcote 1970). In terrestrial studies, a trend of nonuniform distribution of seeds in profiles has been noted.…”
Section: Changes In Seed Densitysupporting
confidence: 54%